PERAN MEDIA PEMBELAJARAN KAHOOT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V DI SDIT ATIKAH MUSADDAD - Rivani Anjayani; Ejen Jenal Mutaqin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of Kahoot! as a learning media in improving students’ learning motivation at SDIT Atikah Musaddad, as well as to analyze its advantages and disadvantages in the learning process. This research employed a qualitative method with a literature review approach. Data were collected from various relevant sources, including books, scientific journals, and research articles related to learning media, learning motivation, and the use of technology in education. The data collection technique used documentation study, while the data analysis applied content analysis. The findings indicate that Kahoot plays a significant role in enhancing students’ learning motivation by increasing active participation, creating an enjoyable learning atmosphere, providing immediate feedback, and improving students’ focus and concentration. Furthermore, Kahoot supports the implementation of student-centered learning, which aligns with constructivist theory and the Merdeka Curriculum. However, the use of Kahoot also has several limitations, such as dependence on internet connectivity, limited access to digital devices, and the potential distraction caused by excessive focus on game elements. In conclusion, Kahoot is an effective learning media for improving students’ motivation when implemented appropriately and supported by adequate facilities and instructional strategies.